Contralateral muscle fatigue from slow, isokinetic contractions is not velocity-specific - Duffett, C. A.; Wiseman, S. A.; Punjabi, A.; Power, K. E.; Behm, D. G. (The Journal of Sport and Exercise Science, 2022)
Non-local muscle fatigue (NLMF) describes exercise-induced fatigue of non-exercised muscles. An unexplored aspect of NLMF is whether the effects are velocity specific. In a randomized, crossover design, unilateral fatigue (4-sets of 15 maximal repetitions, separated by 15sec) was induced with low velocity (600.s-1), reciprocating, isokinetic knee extensions (KE) and flexions (KF) or participants rested in the control conditions. Possible NLMF was tested with contralateral KE and KF maximal isokinetic discrete (single contraction) and repeated repetitions force and electromyography (EMG) when measured with low (12 repetitions at 60°.s-1, slow) or high (48 repetitions at 240°.s-1, fast) velocity conditions. Sixteen (10 males and 6 females) participants attended the laboratory on four occasions. Participants either rested (control) or were unilaterally fatigued prior to completing either the slow (60°.s-1) or fast (240°.s-1) testing conditions. The discrete KE and KF forces and EMG were not significantly different from control, with no significant relative force differences at 60°.s-1 or 240°.s-1. A significant condition effect revealed that the intervention conditions fatigue index during the KE and KF repeated maximal test significantly decreased 11% (p = .02, Effect Size: ES = 0.34) and 10% (p = .005, ES = 0.41) more respectively than the two control conditions. This study highlights that prior slow maximal isokinetic, unilateral, dominant KE and KF fatigue did not demonstrate decreases or velocity specific testing effects with singular maximal force, with some evidence of NLMF with fatigue endurance in the contralateral muscles